Web 2.0 and Semantic Web perspective for Public Relations - Mylona, Ifigeneia; Amanatidis, Dimitrios (Qualitative and Quantitative Methods in Libraries, 2019)
Until recently, public relations were based on the personal relations of public relations executives but also on the use of traditional means of mass media. With the advent of new technologies such as the World Wide Web, a significant thrust of new opportunities and possibilities emerged. As internet technologies constitute cutting edge technologies, they naturally evolve and improve. The aim of this article is to examine how recent advances in web technology such as Web 2.0 and Semantic Web can facilitate public relations executives to accomplish their strategic tasks more effectively. An initial investigation of the definition of these two trends will contribute to answering questions such as: Do these technologies really help public relations executives or are they in fact much ado about nothing? Do the public relations executives continue to use the old practices or do they replace them with new ones?